Spots and Flares in Hot Main Sequence Stars Observed by Kepler, K2, and TESS - Balona, Luis A. (Frontiers in Astronomy and Space Sciences, 2021)
About 22000 Kepler stars, 7000 K2 stars and nearly 60000 TESS stars from sectors 1–24 have been classified according to variability type. A large proportion of stars of all spectral types appear to have periods in their light curves consistent with the expected rotation periods. A previous analysis of A- and late B-type stars suggests that these stars are indeed rotational variables. In this paper we have accumulated data to show that rotational modulation is present in about 30–40 percent of A- and B-type stars. A search for flares in TESS A- and B-type stars resulted in the detection of 102 flares in 57 stars. Analysis of flare energies show that the source of the flares cannot be a cool dwarf companion nor a F/G giant. The realization that a considerable fraction of A- and B-type stars are active indicates that a revision of current concepts regarding hot star envelopes is required.